University libraries fighting fake news: an analysis of the knowledge and practices of Portuguese librarians - Sanches, Tatiana (2021)
Problems with fake news are an emerging subject that has been debated in many sectors of society. Libraries are no exception, and particularly university libraries have been taking a stand against this new reality and seeking to combat it, especially through information literacy training programs. Several studies have already concluded that training that soaks critical thinking in the use of information can benefit users; it enables them to strengthen their strategies for distinguishing informational truth from fake news, misinformation, deceived, or misleading information. Inspired by research carried out in Spain, this study seeks to understand what knowledge Portuguese librarians have about this subject and what strategies are being prepared or implemented by academic libraries in Portugal to combat fake news and misinformation. For this purpose, a questionnaire is applied and addressed to the 172 Portuguese academic libraries registered in a national directory of libraries. The questionnaire comprises data aggregated in four sections: library identification; characterization of knowledge about the subject; good practices in the fight against fake news; and a final open question. Seventy-three libraries answered, representing 43% of the universe under analysis. The results show a thorough knowledge of the issue by librarians, but still incipient actions regarding practices that directly address the fight against fake news, through information literacy training.